THE USE OF ACCOUNTING APPS VIA MOBILE CLOUD COMPUTING IN ROMANIA - TUDORAN, Laura Elena; IONESCU, Bogdan Ștefan (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
In a world in perpetual motion and transformation, mobile devices tend to be communications universal remedy applicable throughout many spheres of activity. Mobile devices are different from each other, depending on the information processing capacity, storage capacity, keyboard, screen, battery life and communication bandwidth. As cloud-based accounting solutions are serving consumers and users of financial accounting information we chose to evaluate the user experience of SaaS financial applications accessed from mobile devices from the perception PhD students participating in doctoral programs organized by the Academy of Economic Studies in Bucharest.